Nontargeted mass spectrometry of dried blood spots for interrogation of the human circulating metabolome. (8th July 2021) - Ward, Casey; Nallamshetty, Shriram; Watrous, Jeramie D.; Acres, Eowyn; Long, Tao; Mathews, Ian T.; Sharma, Sonia; Cheng, Susan; Imam, Farhad; Jain, Mohit
Abstract: Advances in high‐resolution, nontargeted mass spectrometry allow for the simultaneous measure of thousands of metabolites in a single biosample. Application of these analytical approaches to population‐scale human studies has been limited by the need for resource‐intensive blood sample collection, preparation, and storage. Dried blood spotting, a technique developed decades ago for newborn screening, may offer a simple approach to overcome barriers in human blood acquisition and storage. In this study, we find that over 4, 400 spectral features across diverse chemical classes may be efficiently and reproducibly extracted and relatively quantified from human dried blood spots using nontargeted metabolomic analysis employing HILIC and reversed‐phase liquid chromatography coupled to Orbitrap mass spectrometry. Moreover, over 80% of metabolites were found to be chemically stable in dried blood spots stored at room temperature for up to a week. In direct relation to plasma samples, dried blood spots exhibited comparable representation of the human circulating metabolome, capturing both known and previously uncharacterized metabolites. Dried blood spot approaches provide an opportunity for rapid and facile human biosampling and storage and will enable widespread metabolomics study of populations, particularly in resource‐limited areas.